Geographic distribution and trends of small-area burn claims in Japan: An analysis using NDB open data from 2014 to 2021 - Takeshi Utsunomiya; Takahiro Ueda (Scars, Burns & Healing)
Introduction Burns are a major global health issue, causing approximately 180,000 deaths annually and leading to high morbidity rates. The Japan Trauma Data Bank Report 2022 recorded 1749 burn cases, with a mortality rate of 17.6%. However, comprehensive national data regarding non-fatal burns and regional differences in Japan are lacking. This study aimed to analyze the distribution of small-area burns among patients across Japanese prefectures using the National Database of Health Insurance Claims and Specific Health Checkups of Japan (NDB). Methods We utilized NDB Open Data from fiscal years 2014 to 2021 to investigate medical claims for small-area burns. The number of claims was normalized to the population of each prefecture using demographic data obtained from eStat, and the correlation between the number of claims and per capita income in each prefecture was assessed. Results The highest number of small-area burn claims was observed among children aged 0–5 years and individuals aged >65 years. Women aged 15–64 years submit approximately twice as many claims as men in the same age group. Significant geographic variations were observed, with more claims in Kochi, Saga, Kumamoto, and Kagoshima and fewer claims in Okinawa, Hokkaido, and Chiba. The number of claims decreased annually, with Saga Prefecture exhibiting the most substantial reduction. There is a significant negative correlation between the number of claims and per capita income. Conclusion The annual decrease in claims corresponds with previous reports of a decreased incidence of burn injuries. Regional differences suggest an influence of local factors on burn incidence. Further research is necessary to explore these regional disparities and to identify effective burn prevention strategies. Lay summary Burns are a major global health problem, causing many injuries and deaths each year. In Japan, severe burns are well-documented, but there is little information about small-area burns that do not require hospitalization. Understanding how often and where these small-area burns occur can help create better prevention strategies. This study aims to understand the frequency and distribution of small-area burns across different regions in Japan and among various age and gender groups. We want to identify which areas have higher or lower rates of small-area burns and observe any trends over time. We used data from Japan's National Database of Health Insurance Claims, covering 2014 to 2021. This database includes information on medical treatments paid for by health insurance. We calculated the number of small-area burns per 1000 people for each prefecture (region) in Japan and analyzed differences based on age and gender. We found small-area burns are most common among young children (aged 0–5) and older adults (over 65). Women aged 15–64 had about twice as many small-area burns as men in the same age group. There were significant regional differences: some areas, like Kochi and Saga, had higher rates of small-area burns, while others, like Okinawa and Hokkaido, had lower rates. Over the years, small-area burns decreased, with Saga showing the most notable reduction. Our study provides valuable insights into the patterns of small-area burns in Japan, which can help in designing targeted prevention efforts. However, we did not investigate the specific reasons behind the regional differences or the decrease in burn cases over time. This underscores the need for further research to understand these factors better and potentially make more significant contributions to public health.